The mechanisms of ferroptosis and its role in alzheimer’s disease - Ma, Hongyue; Dong, Yan; Chu, Yanhui; Guo, Yanqin; Li, Luxin (Frontiers in Molecular Biosciences, 2022)
Alzheimer’s disease (AD) accounts for two-thirds of all dementia cases, affecting 50 million people worldwide. Only four of the more than 100 AD drugs developed thus far have successfully improved AD symptoms. Furthermore, these improvements are only temporary, as no treatment can stop or reverse AD progression. A growing number of recent studies have demonstrated that iron-dependent programmed cell death, known as ferroptosis, contributes to AD-mediated nerve cell death. The ferroptosis pathways within nerve cells include iron homeostasis regulation, cystine (Cys)/glutamate (Glu) reverse transporter (system xc-), glutathione (GSH)/glutathione peroxidase 4 (GPX4), and lipid peroxidation. In the regulation pathway of AD iron homeostasis, abnormal iron uptake, excretion and storage in nerve cells lead to increased intracellular free iron and Fenton reactions. Furthermore, decreased Glu transporter expression leads to Glu accumulation outside nerve cells, resulting in the inhibition of the system xc- pathway. GSH depletion causes abnormalities in GPX4, leading to excessive accumulation of lipid peroxides (LPO). Alterations in these specific pathways and amino acid metabolism eventually lead to ferroptosis. This review explores the connection between AD and the ferroptosis signal pathways and amino acid metabolism, potentially informing future methodologies for AD diagnosis and treatment.